Pembatalan Akta Hibah karena Melanggar Legitimate Portion dalam Kitab Undang-Undang Hukum Perdata: Studi Putusan No. 17/Pdt.G/2021/PN Klb - Ahmad, Aldeo Nur; Budhiawan, Adlin (IAIN Langsa, 2024)
Ideally, the granting of a gift (hibah) should not violate the legitime portie, which is the mandatory portion of the heirs. However, in reality, as seen in Decision No. 17/Pdt.G/2021/PN Klb, the gift exceeded the permissible limit without the approval of the legitimate heirs. This study aims to analyze the legal provisions governing the legitime portie in the Indonesian Civil Code (KUHPerdata) and the impact of canceling the hibah deed on the inheritance of the deceased. This article is categorized as qualitative research with a normative legal approach. The methodology employed is descriptive analytical study. The findings conclude that the legal provisions in the Civil Code, particularly Article 914 paragraph (3), emphasize that a testator may not grant a gift or will that diminishes the legitime portie rights of direct-line heirs. Consequently, gifts that violate this provision, as demonstrated in Decision No. 17/Pdt.G/2021/PN Klb, can be annulled, and the assets previously granted must be returned to the inheritance pool to be fairly distributed in accordance with the rights of the legitimate heirs.